Mechanical and Thermal Characterisation of Millscale Modified Al-Cu Alloy for Artificial Intelligence Systems - Sekunowo, Olatunde Israel; Kuforiji, Catherine U.; Ajibodu, Emmanuel Oluwaseun (Journal of the Institute of Engineering, 2021)
Continuous research into critical functional property enhancement of materials employed in artificial intelligence systems is imperative to overcome performance limitations. This study investigated the thermal and mechanical properties of stir-cast fabricated Al-Cu alloy modified with addition of iron-millscale (IMS) particles varied from 2-6 wt.%. The alloys microstructure was analysed using both optical and scanning electron microscope coupled with energy dispersive spectroscopy (SEM/EDS). PerkinElmer Thermogravimetry/Derivative thermal analyser was used to assess the alloys thermal characteristics while the mechanical properties were evaluated using relevant state of the art equipment. Results show that the best thermal and mechanical properties comparable to established standards were achieved at 6 wt.% IMS particle addition. Contributions to the alloy enhanced performances stemmed from the structure refining propensity of IMS particles. Based on the thermal and mechanical properties demonstrated, the alloy is recommended for application in pneumatic offshore valve actuator used in oil and gas flow process lines.